2006
DOI: 10.1021/jo0601821
|View full text |Cite
|
Sign up to set email alerts
|

Convenient Method of Synthesizing 3-Ethoxycarbonyl Indoles

Abstract: We have developed a convenient two-step procedure for the synthesis of 3-ethoxycarbonyl indoles from commercially available materials. The two-step procedure involves the synthesis of 2-aryl-3-hydroxypropenoic acid ester, followed by a catalytic reduction. This method is efficient, simple, and selective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Starting from Scheme 1 , fragment 2 was inserted at the N-1 position of four different bi-heterocycles that were previously investigated by our research group as N(1)-CO- aryl(alkyl) derivatives: indoles (Crocetti et al, 2016 ), indazoles (Crocetti et al, 2011 , 2013 ), 7-azaindoles (Crocetti et al, 2018 ; Giovannoni et al, 2019 ) and 7-azaindazoles (data not shown). Indole derivatives 3a-c were obtained starting from the precursors 1a-c ( 1a : Shahidul et al, 2006 ; 1b : DeGraw and Goodman, 1964 ; 1c : Yuen et al, 2013 ) by treatment with 4-(chlorosulfonyl)phenyl pivalate 2 and sodium hydride in anhydrous tetrahydrofuran (THF) at room temperature. To obtain the final indazoles 3d-g two different procedures were followed: treatment of the appropriate intermediate 1d-g ( 1d: Alaime et al, 2018 ; 1e,g: Crocetti et al, 2013 ; 1f: Crocetti et al, 2011 ) with the sulfonyl chloride 2 in anhydrous CH 2 Cl 2 and Et 3 N (compounds 3d-f ) or in dry pyridine at room temperature ( 3g ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Starting from Scheme 1 , fragment 2 was inserted at the N-1 position of four different bi-heterocycles that were previously investigated by our research group as N(1)-CO- aryl(alkyl) derivatives: indoles (Crocetti et al, 2016 ), indazoles (Crocetti et al, 2011 , 2013 ), 7-azaindoles (Crocetti et al, 2018 ; Giovannoni et al, 2019 ) and 7-azaindazoles (data not shown). Indole derivatives 3a-c were obtained starting from the precursors 1a-c ( 1a : Shahidul et al, 2006 ; 1b : DeGraw and Goodman, 1964 ; 1c : Yuen et al, 2013 ) by treatment with 4-(chlorosulfonyl)phenyl pivalate 2 and sodium hydride in anhydrous tetrahydrofuran (THF) at room temperature. To obtain the final indazoles 3d-g two different procedures were followed: treatment of the appropriate intermediate 1d-g ( 1d: Alaime et al, 2018 ; 1e,g: Crocetti et al, 2013 ; 1f: Crocetti et al, 2011 ) with the sulfonyl chloride 2 in anhydrous CH 2 Cl 2 and Et 3 N (compounds 3d-f ) or in dry pyridine at room temperature ( 3g ).…”
Section: Resultsmentioning
confidence: 99%
“…To a suspension of the substrate 1a-c (1a: Shahidul et al, 2006 ; 1b: DeGraw and Goodman, 1964 ; 1c: Yuen et al, 2013 ) (0.43 mmol) in 10 mL of anhydrous THF, 0.86 mmol of sodium hydride (60% dispersion in mineral oil) was added while stirring. After 30 min, 0.56 mmol of 4-(chlorosulfonyl)phenyl pivalate 2 (Hwang et al, 2015 ) was added, and the mixture was stirred at room temperature overnight.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Viresh H. Rawal of the University of Chicago arylated 67 the silyl enol ether 147 (Scheme 56) with an ortho -nitrophenyl iodinium salt (NPIF) to give, after reduction, the indole 148 . M. Mahmoun Hossain of the University of Wisconsin, Milwaukee inserted 68 ethyl diazoacetate into the aldehyde 149 (Scheme 57), converting it, via reduction, into the indole 150 .…”
Section: Typementioning
confidence: 99%
“…In 1998, our group developed the synthesis of 3‐hydroxy‐2‐arylacrylates through an unprecedented [1,2]‐aryl shift;6 since then, these substrates have been used as useful precursors for the synthesis of indoles7 and furans 8. Most importantly, however, the presence of aryl‐bound tertiary prochiral carbon centers in these compounds should now allow us to synthesize chiral all‐carbon α‐aryl quaternary stereocenters.…”
Section: Introductionmentioning
confidence: 99%